Enhancing anti-carbonation properties of oil well cement slurry through nanoparticle and cellulose fiber synergy - Lu, Hu (2025)
The anti-carbonation property of oil well cement (OWC) is critical for sealing efficiency of wellbores under geological CO2 sequestration. However, gas migration through OWC around wellbores may lead to a deterioration and failure of the entire storage system. Developing carbon-resistant cement has been the emerging trend in the research community. Previous studies mainly focused on nanoparticles alone to enhance performance of OWC, and the purpose of the research is to explore the synergy of nanoparticles and cellulose fiber (CF) in enhancing engineering properties (e.g., carbonation resistance) of oil well cement slurry. The focus was on investigating compressive strength, permeability, pore structure, and carbonation depth associated with the micro-level texture in a CO2 corrosion environment using X-ray diffraction, Scanning Electron Microscopy, and thermogravimetric analysis methods. Four nanoparticles, namely, nano-SiO2 (NS), nano-TiO2 (NT), nano-Al2O3 (NA), and nano-CaCO3 (NC), were selected for the mixture design. Results indicated that the incorporation of 1∼2 % NPs into the OWC paste resulted in a notable decrease in portlandite and an increase in calcium silicate hydrates, thereby enhancing compressive strength and hydration process. In addition, the single admixture of CF could minimize the formation of cracks in the cement matrix and reduce the average carbonation depth by 54 %. More importantly, the synergy of CF and NP significantly improved the resistance of OWC to carbonation, and the OWC mixed with CF and NS displayed the highest carbonation resistance.